Dinero, circuito, relaciones íntimas - Zelizer, Viviana A. (Sociedad y Economía, 2008)
The dichotomy between intimate and interpersonal relationships stems from a longstanding tradition. As an alternative to this dichotomy, the present article proposes an approach based on the recognition of interpersonal circuits. To illustrate the range of this concept, four areas are taken under consideration: 1) corporate circuits; 2) local currencies; 3) paid personal care, and 4) children's participation in family economies. The author concludes that both intimate and impersonal transactions frequently work through circuits that participants mark off amongst each other through well-established practices, understandings and representations that differ from one circuit to the next.